TECNOLOGIE INTEGRATE PER LA GESTIONE E VISUALIZZAZIONE DEL PAESAGGIO 3D: IL CASO STUDIO DELLA NECROPOLI DELLA BANDITACCIA. - Marsicano, Lucia; Cinquanta, Emanuele; Iaia, Francesco (Archeomatica, 2015)
The project aims to create a 3D model of the Necropolis of Banditaccia in Cerveteri. The site, UNESCO heritage since 2004 , covers an area of 400 hectares. Starting from 2D data, provided by the CNR , it was possible to realize the model . Aim of the work was the return in 3D of the plateau of the necropolis and the creation of a container, metrically correct, in which is possible to place models resulting from laser scanners, photogrammetry and modeling of archaeological items.